THE USE OF OMEGA-3 FATTY ACIDS FOR THE TREATMENT OF PATIENTS WITH CARDIAC ARRHYTHMIAS - A. O. Malygin; V. L. Doshchitsin (Столичная издательская компания, 2015)
Antiarrhythmic effect of omega-3 polyunsaturated fatty acids (ω-3 PUFA), eicosapentaenoic and docosahexaenoic acids in patients with recurrent atrial fibrillation and ventricular arrhythmias had been proven. The positive effect of the ω-3 PUFA on the risk of sudden arrhythmic death and overall mortality in the patients after myocardial infarction and patients with chronic heart failure had been also proven.